Effects of carbon and nitrogen nutrition characteristics in vegetative parts on grain yield in maize - Shi, Lin; Liao, Linzheng; Chen, Guowei; Wang, Yuping; Tan, Yanzhi; Zhang, Yahan; Yu, Fang; Lin, Meng; Li, Qiang; Ren, Yun; Yin, Xuewei (Frontiers in Plant Science, 2026)
We investigated the effects of nitrogen application on carbon and nitrogen nutrition characteristics of maize nutritional organs and grain yield, and clarified the relationship between carbon and nitrogen nutrition characteristics of maize nutritional organs and grain yield. The field trials were conducted from 2019 to 2020. The nitrogen-efficient Zhenghong 311 (ZH 311) and nitrogen-inefficient Xianyu 508 (XY 508) varieties were used as experimental materials. We used four nitrogen fertilizer rates (0, 120, 240, and 360 kg ha−1), labeled as N1-N4 (with N1 being the 0 kg N ha−1 control). The results indicated that synergistic regulation of carbon-nitrogen metabolism plays a crucial role in yield formation, and the rationale lies in the differential responses of maize varieties to nitrogen levels, with key findings showing that ZH 311 achieves high yield under moderate nitrogen (N) conditions while XY 508 depends on high N supply. At maturity, ZH 311 exhibited a higher nitrogen content in culm sheaths, leaves, and ears than XY 508, whereas root nitrogen content was lower than that of XY 508. However, carbon content differences among organs at maturity were not significant between varieties, resulting in lower C/N ratios in ZH 311 organs at maturity than those in XY 508. The C/N ratios in maize nutritional organs were negatively correlated with yield, indicating that maintaining a low nutritional organ C/N ratio is a key mechanism for nitrogen-efficient varieties to achieve higher yields than nitrogen-inefficient varieties. Nitrogen application significantly increased carbon and nitrogen accumulation in the maize nutritional organs. However, the increase in all organs was greater in XY 508 than in ZH 311, indicating that additional nitrogen fertilizer is more beneficial for enhancing carbon and nitrogen accumulation in the nutritional organs of nitrogen-inefficient varieties. Moreover, nitrogen-inefficient varieties require higher nitrogen application rates to maintain carbon and nitrogen accumulation. However, nitrogen-efficient varieties exhibited substantially higher carbon and nitrogen accumulation in the organs than the nitrogen-inefficient varieties at identical nitrogen levels. Correlation analysis revealed that carbon and nitrogen accumulation in the nutritional organs were positively correlated with grain yield at maize maturity. Leaf nitrogen accumulation (R² = 0.8641**) showed the strongest correlation with grain yield, whereas stem sheath carbon accumulation (R² = 0.8257**) exhibited the highest correlation with grain yield.